(untitled) (Jahangirnagar University Environmental Bulletin, 2013)
Effects of pesticide exposure on farmers health are conducted mostly in developed countries, which is rare in least developed countries like Bangladesh. Here farmers had less guidance and instruction about the preventive measures to protect themselves and environment. This work was studied to assess the impacts of pesticide exposure on the paddy farmers health in two different Upazilas of Manikganj, Bangladesh. The study was conducted as cross-sectional study with quantitative and qualitative components. Five hundred eighty two farmers (368 sprayers and 214 non-sprayers) were interviewed. Chi-squared tests and multinomial logistic regression analysis were performed for statistical analysis. Three hundred sixty eight farmers (64.3%) sprayed pesticides and were directly exposed to chemicals. Among them 64.22% and 9.06%, farmers used moderately and highly hazardous pesticides, respectively. 257 farmers (69.8%) were not taken any protective measures to handle pesticides. Excessive sweating, burning eyes and fatigue were reported by 26.3%, 24.4% and 18.8% of the farmers, respectively. These types of symptoms were significantly associated among male farmers. The study reveals that due to lack of awareness, occupational exposures of pesticides among farmers are common in Bangladesh and it also emphasize the importance of use of personal protective equipments. Jahangirnagar University Environmental Bulletin, Vol.2, 18-25, 2013 DOI: http://dx.doi.org/10.3329/jueb.v2i0.16326